2018
DOI: 10.1029/2018ja025991
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Last Closed Drift Shells for the 2013 GEM Radiation Belt Challenge Events

Abstract: Radiation belt behavior is often analyzed in terms of adiabatic invariants, of which the third roughly characterizes the radial distance of particle drift shells. The outermost, or last closed drift shell, can be an important boundary for numerical modeling, especially for drift-averaged treatments such as three-dimensional diffusion codes. Here we discuss calculation of the last closed drift shell, using the widely used International Radiation Belt Environment Modeling (IRBEM) Library, the LanlGeoMag code, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 47 publications
3
63
0
Order By: Relevance
“…Albert et al. (2018) studied several codes to calculate the LCDS in different magnetic field models for four different disturbed periods and concluded that, nevertheless, they produce seemingly reasonable and similar results. Moreover, it must be underlined that magnetic field models, such as TS07, are empirical approximations of the real field during geomagnetic disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Albert et al. (2018) studied several codes to calculate the LCDS in different magnetic field models for four different disturbed periods and concluded that, nevertheless, they produce seemingly reasonable and similar results. Moreover, it must be underlined that magnetic field models, such as TS07, are empirical approximations of the real field during geomagnetic disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…This is understandable. On the one hand, the L * corresponding to the last closed drift shell is lager at larger K due to drift shell splitting (Albert et al, ; Roederer & Zhang, ). On the other hand, electrons drift period, which is a proxy of the lifetime for magnetopause‐loss (e.g., Tu et al, ), is longer for electrons of larger K .…”
Section: Discussionmentioning
confidence: 99%
“…Outer zone electron dropout events are a common feature of geomagnetic storms, particularly at higher L shells (e.g., Green Onsager et al, 2002;Shprits et al, 2006;Su et al, 2017;Turner, Angelopoulos, Morley, et al, 2014;Ukhorskiy et al, 2015;Xiang et al, 2017). Rapid radial loss is observed with CME shock-driven storms (Hudson et al, 2014) and well correlated with the last closed drift shell during strong magnetopause compression (Albert et al, 2018;Olifer et al, 2018). Drift shell splitting is enhanced during such events wherein electrons near 90°pitch angle move to larger radial distance on the dayside conserving their first adiabatic invariant (Roederer, 1967(Roederer, , 1970, and may be preferentially lost to the magnetopause.…”
Section: Radial Lossmentioning
confidence: 99%